Ab Initio and DFT Investigation of Effect of Substituent at the C7 Position of 4-AminoDANA Sialidase Inhibitor: Pharmaceutical Science-Chemistry - Chandrasekaran, Krishnan (International Journal of Life Science and Pharma Research, 2022)
Sialic acid is the active site of neuraminidase protein, eventually it cleaves form its substrate via sialsyl cation intermediate and proliferates the viral infection to other cells. On account of weak binding affinity between substrate and receptor, the viral infection communicates to other cells and leads to mortality of humans. DANA is the first sialidase inhibitor formed by the dehydration of the C2 hydroxyl group of sialic acid. The replacement of hydroxyl group at C4 position of DANA by an amino group drastically increases the binding affinity and results 4-amino-DANA inhibitor, which is potent than parent DANA. Crystal structure of DANA shows that several binding sites remain free and it should be explored for more powerful sialidase inhibitors. The current study systematically investigates the effect of substituent on the C7 position of 4-amino-DANA in gas phase and solvent phase as well. X-Ray crystallographic study reveals that the C7 of glycerol side chain remains free. Hence, substituent effect at C7 analysis is carried in search of potent sialidase inhibitors. The ab initio and DFT investigation reveals that guanidino and methyl group at C7 position drastically increases the binding affinity between substrate and receptor. Hence further investigation of methyl and guanidine derivatives of the 4-amino-DANA could act as a promising candidate for the design and development of sialidase inhibitors. Vaccination for the H1N1 is not effective due to the new viral mutagenic strains and hence, it cannot contain the viral infection.Therefore antiviral drugs will address the limitation of vaccination. The current finding of sialidase antiviral inhibitors will effectively contain the viral infection and prevent the morbidity